Effects of Nutritional and Socioeconomic Status on Puberty - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The onset of puberty is determined by genetic and environmental factors like socioeconomic and nutritional status. Previous studies have shown a disparity in the effect of socioeconomic factors on menarche and sexual maturation.Aim:This study was carried out to determine the effect of nutrition and socioeconomic status (SES) on puberty.Settings and Design:It is a descriptive, cross-sectional study among adolescent female secondary school students in Abeokuta, Nigeria.Materials and Methods:Subjects selected responded to questions on the proforma. Body mass index (BMI) was calculated from weight and height that were measured.Statistical Analysis:The data were analyzed using Microsoft ExcelR(Microsoft Corporation SP2 software microsoft office 2010 professional plus (PC) Intel Corporation's 386 microprocessor Redmond, Washington, USA) 2010 and SPSS 22.0 (SPSS Inc., Illinois, USA).Results:Participants' mean age and BMI were 14.4 ± 1.9 years and 19.1 ± 2.9 kg/m2, respectively. Subjects from high socioeconomic class (SEC) attained puberty and menarche earlier (12.0 ± 1.5 and 12.9 ± 1.5 years) than those from low SEC (13.5 ± 1.3 and 13.7 ± 1.1 years). These were statistically significant for breast development and menarche. Nutritional status had a negative correlation (r = -0.098) with menarcheal age but positive with pubic hair (r = 0.702) and breast development (r = 0.306).Conclusion:The mean age of menarche occurred earlier in this study when compared to most previous studies in Nigeria. Improved SES and nutritional status influenced the early age of onset of puberty and attainment of menarche.